Prevalence and Associated Factors of Treatment Regimen Fatigue Among People Living with HIV/AIDS in China: A Cross-Sectional Survey - Liu B; Yang Y; Zhou H; Liu H; Xu Z (Patient Preference and Adherence)
Baohua Liu,1,* Yisi Yang,2,* Hongguo Zhou,3 Huan Liu,4 Zhenzhen Xu1 1Department of Elderly Care and Management, School of Health Services and Wellness, Ningbo College of Health Sciences, Ningbo, Zhejiang, People’s Republic of China; 2Institute for STD and HIV/AIDS Prevention and Control, Harbin Center for Disease Control and Prevention, Harbin, Heilongjiang, People’s Republic of China; 3Dean’s Office, Ningbo College of Health Sciences, Ningbo, Zhejiang, People’s Republic of China; 4School of Health Management, Harbin Medical University, Harbin, Heilongjiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongguo Zhou; Huan Liu, Email zhou840512@163.com; liuhuan00813@163.comIntroduction: Treatment regimen fatigue (TRF) is universal among people living with HIV/AIDS. Long-term adherence to treatment regimens is crucial to maintaining the health and life span of such individuals.Objective: This study aimed to examine treatment regimen fatigue among people living with HIV/AIDS and the relevant factors.Methods: This cross-sectional study was conducted between January and December 2019 at two designated AIDS medical institutions in Harbin, China. A total of 717 valid samples were included in the study. The Treatment Regimen Fatigue Scale was used to measure treatment regimen fatigue. The participants responded to several questions regarding their demographic characteristics, clinical characteristics, and social psychological characteristics. Multivariate logistic regression assessed the relationship between TRF and associated factors. Odds ratios (OR) and 95% confidence intervals (CI) for OR were calculated.Results: The self-reported mean global score for the TRFS was − 15.59 ± 22.90. After adjusted location, education background and, monthly income, the logistic regression model indicated that depression (OR=3.177, 95% CI=2.180– 4.629), other chronic diseases (OR=1.786, 95% CI=1.057– 3.019), > 3 years of treatment (OR=1.767, 95% CI=1.203– 2.594), having an intimate confidant (OR=0.514, 95% CI=0.347– 0.760), life satisfaction (OR=0.564, 95% CI=0.365– 0.870), living area (OR=0.491, 95% CI=0.295– 0.817), and an undergraduate or above education level (OR = 0.568, 95% CI=0.335– 0.965) were associated factors for TRF.Conclusion: The prevalence of TRF among PLWHA in China is relatively high and is influenced by multiple factors including psychosocial, clinical, and demographic characteristics. Social support, especially psychological support, for PLWHA should be strengthened. This study’s findings highlight the need to develop multilevel interventions to reduce TRF, addressing the complex needs of PLWHA and mitigating the adverse impact of TRF on HIV treatment outcomes. Further longitudinal research on factors of TRF should be conducted to strengthen and broaden the current findings.Keywords: treatment regimen fatigue, antiretroviral therapy adherence, HIV/AIDS, psychosocial factors